Estimation of PEX1-mediated Zellweger spectrum disorder births and population prevalence by population genetics modeling - Karen E. Malone; Catherine Argyriou; Evelyn Zavacky; Nancy Braverman (Genetics in Medicine Open)
Purpose: Zellweger Spectrum Disorder (ZSD) is a rare syndromic disorder characterized by impaired peroxisome assembly and function. Many cases are due to pathogenic variants in the PEX1 gene and are inherited in an autosomal recessive manner. As with many rare diseases, understanding the disease burden and scale of unmet need is challenging but required to support diagnosis, disease management, and development of therapies. We present a population-genetics-based model to estimate births and overall disease prevalence for patients in the United States, European countries, and Japan. Methods: We utilized large-scale genetic diversity data sets to estimate the mutational burden per region and integrated genotype-phenotype relationships with real-world survival data to provide patient number estimates for severe, intermediate, and mild segments per age and country. Results: We observed regional differences in the variant landscapes expected to contribute to PEX1-mediated ZSD (PEX1-ZSD). Conservative prevalence estimates for the United States, United Kingdom, Germany, France, Italy, Spain, and Japan based solely on known pathogenic variants indicates nearly 500 patients in total. Incorporating predicted pathogenic variants into our model suggests an additional 260 patients with intermediate phenotype and 930 patients with mild phenotype, under the age of 30, across these countries. Conclusion: Notably, our model indicates that a significant proportion of patients with intermediate/mild phenotype may go unrecognized by current diagnostic practices. This diagnosis independent model of patient number estimates provides additional insights into the broad spectrum of PEX1-ZSD on a more global scale and can be used to inform health care strategies for these patients.